Establishment of dorsal-ventral polarity of the Drosophila egg requires capicua action in ovarian follicle cells. - Goff, D.J.; Nilson, L.A.; Morisato, D. (Development, 2001)
The dorsal-ventral pattern of the Drosophila egg is established during oogenesis. Epidermal growth factor receptor (Egfr) signaling within the follicular epithelium is spatially regulated by the dorsally restricted distribution of its presumptive ligand, Gurken. As a consequence, pipe is transcribed in a broad ventral domain to initiate the Toll signaling pathway in the embryo, resulting in a gradient of Dorsal nuclear translocation. We show that expression of pipe RNA requires the action of fettucine (fet) in ovarian follicle cells. Loss of maternal fet activity produces a dorsalized eggshell and embryo. Although similar mutant phenotypes are observed with regulators of Egfr signaling, genetic analysis suggests that fet acts downstream of this event. The fet mutant phenotype is rescued by a transgene of capicua (cic), which encodes an HMG-box transcription factor. We show that Cic protein is initially expressed uniformly in ovarian follicle cell nuclei, and is subsequently downregulated on the dorsal side. Earlier studies described a requirement for cic in repressing zygotic target genes of both the torso and Toll pathways in the embryo. Our experiments reveal that cic controls dorsal-ventral patterning by regulating pipe expression in ovarian follicle cells, before its previously described role in interpreting the Dorsal gradient.